BERKERABAT DI PASAR: KUASA DAN PRAKTIK KEBERAGAMAN AGAMA DI MAUMERE, NUSA TENGGARA TIMUR - De Porres, Martin Elvanyus (Jurnal Studi Agama dan Masyarakat, 2023)
This study explains the background to the acculturation process of Muslims and Christians in Maumere, Flores, East Nusa Tenggara, in relation to the influence of economic and political power. As a contribution to the study of religious dialogue in Indonesia, this research starts from a historical explanation of patterns in terms of religious assimilation, and then looks at the conduction of power practices in this acculturation. This study is qualitative data research using library methods. Data from books, journals, newspapers and the internet are analyzed to provide a description of the development of relations between religious communities. In contrast to a number of previous studies on Nusa Tenggara which viewed the home as the binding root of multiculturalism and religious diversity, this study finds that the existence of the market actually plays an important power role in the acculturation process in question. This condition began with traditional economic exchange activities between Bajo and Bugis sailors and traders with residents of the plains, then culminated in the facts of political governance during the reign of the Dutch East Indies. Tolerance from below, which is centered on economic factors, can spark further discussion to look at the social relations of religious communities in Indonesia in general.